Modeling and analysis of articulated steering mechanism. (2022) - Sreeharsha, R.; Kumar, N.; Kumar, Ajit; Tripathi, J.P.
Abstract: The current article deals with the dynamic analysis of closed-loop controlled orbitrol steering unit. Mathematical model of the steering system is developed in MATLAB environment and results are well validated with the experimental results. The experimental setup is equipped with the conventional PID controller. Comparison analysis has been performed for different steering position command profiles. It is observed from the comparative analysis that the developed system performs well and offers satisfactory response for a diverse range of positioning requirements.